PENGARUH STARTER BAKTERI ASAM LAKTAT PROBIOTIK TERHADAP PERUBAHAN KIMIAWI DAN MIKROBIOLOGIS RUSIP - Pebry Aisyah Putri Batubara; Desniar Desniar; Iriani Setyaningsih (Jurnal Teknologi dan Industri Pangan, 2019)
Rusip is one of the fish fermentation products. Traditional rusip made by Bangka Belitung community do not have a specific standard which leads to the high variety ofquality. One of the efforts to improve the quality of rusip is the addition of lactic acid bacteria (LAB) as a starter culture. This research aims to study the effect of the addition of starter culture combinations on the chemical and microbiological changes of the rusip and toobtain the best combination of LAB starters in rusip fermentation. This research used anchovy fish (Stolephorus sp) and 5% ofLAB starter combination consisting of Lactobacillus plantarum SK(5) and L. plantarum NS(5), L. plantarum NS(5) and L. plantarum NS(9) and L. plantarum NS(9) and L. plantarum SK(5) 5%. In addition, 5% ofsalt (w/w) and 5% of palm sugar (w/w) were added. The fermenta-tions were conducted for 8 days. The research were conducted in three stages: 1) starter culture prepara-tion; 2) raw material (fish) preparation; and 3) application of starter culture during rusip fermentation. The results showed that raw materialscontained a total microbe of 3.0x104 CFU/g, non detectable levels ofLAB, 6.54of pH and 20.40 mg N/100g of total volatile bases (TVB). After fermentation, the rusip contained total LAB of7.64-9.24log CFU/g, 0.86-3.98% of total lactic acid,4.22-6.36 of pH, 0.32-1.39 of free amino acid and 5.34-5.44% of salt.The best rusip was produced bya combination of L. plantarum SK(5) and L. plantarum NS(5) and con-tained12.36 g/100g of total amino acid.